2016
DOI: 10.1002/jqs.2909
|View full text |Cite
|
Sign up to set email alerts
|

A map of Pleistocene aeolian deposits in Western Europe, with special emphasis on France

Abstract: International audiencehe Land Use and Cover Area frame Statistical survey (LUCAS) database on topsoil properties inEurope was used to map aeolian deposits. The points which satisfy the grain-size criteria of coversands, loess andtransitional facies were extracted from the rasters of predicted soil texture established by kriging of the LUCAS databy Ballabio et al. (2016). A comparison with already available maps, derived from a conventional field approach,shows a good fit in most of the tested areas. The new map,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 46 publications
3
49
2
2
Order By: Relevance
“…Soil texture information was included from the maps produced by Ballabio et al (), and from data on aeolian deposits (Bertran et al , ). Seismic data were obtained from the Si‐Hex catalogue, which lists earthquakes recorded between 1962 and 2009 (http://www.franceseisme.fr, Cara et al , ), from the SisFrance database (BRGM/IRSN/EDF, version 2015) for earthquakes since the year 463 (http://www.sisfrance.net), and from NEOPAL (BRGM, last update 2009) for palaeoseismicity indices (http://www.neopal.net / ).…”
Section: Methodsmentioning
confidence: 99%
“…Soil texture information was included from the maps produced by Ballabio et al (), and from data on aeolian deposits (Bertran et al , ). Seismic data were obtained from the Si‐Hex catalogue, which lists earthquakes recorded between 1962 and 2009 (http://www.franceseisme.fr, Cara et al , ), from the SisFrance database (BRGM/IRSN/EDF, version 2015) for earthquakes since the year 463 (http://www.sisfrance.net), and from NEOPAL (BRGM, last update 2009) for palaeoseismicity indices (http://www.neopal.net / ).…”
Section: Methodsmentioning
confidence: 99%
“…This area remained unglaciated during the Pleistocene cold periods but experienced phases of permafrost development. Because of limited loess deposition (the area was at the southern margin of the north European loess belt; Bertran et al, 2016), remnants of periglacial landscapes are still easily readable in aerial photographs and most of the polygons caused by thermal contraction cracking of the ground and soil stripes caused by active layer cryoturbation found in France from aerial survey are concentrated in this latitudinal band (Andrieux et al, 2016a). Single grain OSL dating of the infilling of sand wedges and composite wedge pseudomorphs from sites located in the Loire valley showed that thermal contraction cracking occurred repeatedly during Marine Isotopic Stages (MIS) 4, 3, 2, and early MIS 1 (Younger Dryas) (Andrieux et al, 2018).…”
Section: Geomorphological Context Of the Study Regionmentioning
confidence: 99%
“…Dunes, coversands and loess covers occur abundantly in the European lowlands and are important elements of the European Sand Belt (ESB; Koster 1988Koster , 2009). These landforms and sediments formed during glacial events, when a decrease in precipitation, a scarcity of vegetation, and increasing wind speeds and frost abrasion resulted in a large amount of material being deposited from off the Scandinavian Ice Sheet (SIS) (Bertran et al 2016).…”
Section: Introductionmentioning
confidence: 99%